Teaching design from the identity speech of the country brand – Ecuador - Arias Villamar, John Alfredo (Scripta Mundi, 2022)
The research is based on the teaching of design, from the discourse of national character or country brand, and how it contributes to the resolution of visual problems; and significantly guides the selected student body. Three stages of materialization were established: Stage 1 of theoretical and practical research, where the visual arguments related to the country brand, visual identity, identity morphology, identification strategies, morphological characteristics and high performance indicators were analyzed. Stage 2, There were materialized the visual identities, under analog and digital graphic techniques; and stage 3, in which the proposal was submitted.
Keywords: Country brand; teaching; graphic design; identity discourse